2013
DOI: 10.1371/journal.pone.0082654
|View full text |Cite
|
Sign up to set email alerts
|

Selective Vulnerability of Spinal and Cortical Motor Neuron Subpopulations in delta7 SMA Mice

Abstract: Loss of the survival motor neuron gene (SMN1) is responsible for spinal muscular atrophy (SMA), the most common inherited cause of infant mortality. Even though the SMA phenotype is traditionally considered as related to spinal motor neuron loss, it remains debated whether the specific targeting of motor neurons could represent the best therapeutic option for the disease. We here investigated, using stereological quantification methods, the spinal cord and cerebral motor cortex of ∆7 SMA mice during developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 61 publications
7
41
0
Order By: Relevance
“…On average, DMSO-treated SMAΔ7 animals have fewer MNs compared to DMSO-treated wild-type animals (13.5 versus 22.7 ChAT+ MNs per 10 μm section; p = 0.0028), similar to previous reports (d’Errico et al, 2013; Mentis et al, 2011). Importantly, we observed that GUA treatment increased the number of ChAT + MNs by an average of 40 (± 5) % in SMAΔ7 animals compared to DMSO-treated animals ( p = 0.034; Figure 7G), indicating that GUA prevents degeneration of spinal MNs by inhibition of ER stress.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…On average, DMSO-treated SMAΔ7 animals have fewer MNs compared to DMSO-treated wild-type animals (13.5 versus 22.7 ChAT+ MNs per 10 μm section; p = 0.0028), similar to previous reports (d’Errico et al, 2013; Mentis et al, 2011). Importantly, we observed that GUA treatment increased the number of ChAT + MNs by an average of 40 (± 5) % in SMAΔ7 animals compared to DMSO-treated animals ( p = 0.034; Figure 7G), indicating that GUA prevents degeneration of spinal MNs by inhibition of ER stress.…”
Section: Resultssupporting
confidence: 89%
“…Previous studies have shown that MN soma sizes are significantly smaller in SMAΔ7 mice as early as PND4 (d’Errico et al, 2013), suggesting that MNs are undergoing atrophy and large MNs are lost even when the animals are pre-symptomatic. We also found that DMSO-treated SMAΔ7 MNs were significantly smaller than DMSO-treated wild-type MNs (220 ± 25 μm 2 in SMA and 316 ± 27 μm 2 in WT; p = 0.0092).…”
Section: Resultsmentioning
confidence: 97%
“…Only ChAT+ neurons located in a position congruent with that of motoneuron groups were counted [13]. All ChAT + profiles located in the ventral horns of immunostained sections and clearly displayed in the plane of section were counted.…”
Section: Quantification Of Histological Resultsmentioning
confidence: 99%
“…Similarly, myofiber number was also increased (1,690 to 2,411 myofibers per section) with ML372 treatment ( Figure 4C). Loss of motor neurons is very rapid in the early postnatal stages of this SMA mouse model, with limited motor neuron loss after PND7 (24,25). Nissl staining of lumbar spinal cord segments ( Figure 4D) showed that ML372 increased motor neuron size ( Figure 4E, mean somatic diameter of 37.2 μm compared with 32.9 μm in vehicle-treated animals), with no change in the number of motor neurons ( Figure 4F).…”
Section: Ml372 Is Brain Penetrant and Has A Reasonable Exposure And Hmentioning
confidence: 93%